2020
DOI: 10.1371/journal.ppat.1008482
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the intracellular localization, protein associations and artemisinin resistance properties of Plasmodium falciparum K13

Abstract: The emergence of artemisinin (ART) resistance in Plasmodium falciparum intra-erythrocytic parasites has led to increasing treatment failure rates with first-line ART-based combination therapies in Southeast Asia. Decreased parasite susceptibility is caused by K13 mutations, which are associated clinically with delayed parasite clearance in patients and in vitro with an enhanced ability of ring-stage parasites to survive brief exposure to the active ART metabolite dihydroartemisinin. Herein, we describe a panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
121
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(133 citation statements)
references
References 88 publications
12
121
0
Order By: Relevance
“…Increased artemisinin resistance has been found in P. falciparum parasites with Pfkelch13 mutations ( Miotto et al, 2015 ; Ariey et al, 2014 ; Ghorbal et al, 2014 ; Straimer et al, 2015 ; Mbengue et al, 2015 ). A previous study found that PfKelch13 could modulate the level of a signaling molecule phosphatidylinositol 3-phosphate (PI(3)P) through interaction with PfPI3K ( Mbengue et al, 2015 ), while other studies did not detect the interaction between PfKelch13 and PfPI3K ( Siddiqui et al, 2020 ; Gnädig et al, 2020 ; Birnbaum et al, 2020 ). PfKelch13 mutations have been linked to the accumulation of PI(3)P in P. falciparum -infected RBCs and this increased PI(3)P level is highly correlated with parasite resistance to artemisinin ( Mbengue et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increased artemisinin resistance has been found in P. falciparum parasites with Pfkelch13 mutations ( Miotto et al, 2015 ; Ariey et al, 2014 ; Ghorbal et al, 2014 ; Straimer et al, 2015 ; Mbengue et al, 2015 ). A previous study found that PfKelch13 could modulate the level of a signaling molecule phosphatidylinositol 3-phosphate (PI(3)P) through interaction with PfPI3K ( Mbengue et al, 2015 ), while other studies did not detect the interaction between PfKelch13 and PfPI3K ( Siddiqui et al, 2020 ; Gnädig et al, 2020 ; Birnbaum et al, 2020 ). PfKelch13 mutations have been linked to the accumulation of PI(3)P in P. falciparum -infected RBCs and this increased PI(3)P level is highly correlated with parasite resistance to artemisinin ( Mbengue et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, the most prevalent SEA K13 mutation, C580Y, was fitness neutral in vitro when gene edited into recent Cambodian clinical isolates, whereas it displayed a significant growth defect when introduced into ART-susceptible parasites isolated before ARTs were widely deployed (34,36). Recently, it has been demonstrated that PF K13 localizes to the parasite cytostomes and other intracellular vesicles and plays a role in parasite hemoglobin endocytosis and trafficking to the lysosome-like digestive vacuole (37)(38)(39). K13 mutations are thought to lead to a partial loss of protein function, which subsequently impairs hemoglobin endocytic uptake, thereby lessening ART activation and conferring ART resistance (37).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, recent data confirm the association of key resistance-mediator K13 with Rab-GTPases [25], adding to the repertoire of proteins comprising K13-mediated endocytic vesicles, and by extension supporting the role of prenylation in K13-mediated processes associated with ART MOA.…”
Section: Discussionmentioning
confidence: 61%